Ways to protect against computer viruses (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
This article lists computer viruses, the damage they can cause to users and computers, and how to protect against viruses like this.